Marketing Management and Information Technology / Second Edition - Fletcher Keith (Prentice Hall, 1995)
This book gives a critical insight into the major marketing concepts and techniques and shows how information technology has the potential to change the marketing manager's job. Overview of Marketing and the Impact of IT, IT and Marketing, What is Marketing, The Changing Marketing System and Environment, Marketing Information for decisions, IT and Marketing Strategy, IT and Marketing Management, Planning for Innovation, New Product Decisions, Product Policy Decisions, Communication Decisions, Sales Decisions, Place Decisions, IT and the Future.